2013
DOI: 10.1007/s10198-013-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rebate contracts on the health care system

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When there are multiple preferred suppliers for the same chemical substance, pharmacies are allowed to choose among preferred brands. By law, pharmacies are allowed to dispense drugs from a non-preferred supplier only (a) if an attending physician explicitly prescribes a specific brand, (b) in situations of proven supply difficulties, or (c) if a patient pays the full price of a nonpreferred drug [13]. However, since regulation is not fully enforced, pharmacies have some discretion in their dispensing.…”
Section: Background On Preferred Supplier Contractsmentioning
confidence: 99%
“…When there are multiple preferred suppliers for the same chemical substance, pharmacies are allowed to choose among preferred brands. By law, pharmacies are allowed to dispense drugs from a non-preferred supplier only (a) if an attending physician explicitly prescribes a specific brand, (b) in situations of proven supply difficulties, or (c) if a patient pays the full price of a nonpreferred drug [13]. However, since regulation is not fully enforced, pharmacies have some discretion in their dispensing.…”
Section: Background On Preferred Supplier Contractsmentioning
confidence: 99%
“…A more fine-grained analysis of various age groups has revealed that this is largely driven by economists who are older than 45. In contrast, a journal's Handelsblatt only positively influences a journal's reputation for economists aged 55 and younger.…”
Section: Estimation Results For Different Age Groupsmentioning
confidence: 99%
“…GPOs are prone to kickbacks/sharebacks, significant profit-taking from both manufacturers and hospitals, and are a major cause of the lack of transparency in the supply chain. 2 Despite the strong claims made by the GPO industry relative to the savings derived from consolidation (Jayaraman et al, 2014), several extensive reviews of the healthcare contracting literature fails to find a single study documenting the existence of a relationship between a higher volume of purchases and cost savings (Dobryzkowski et al, 2014; Graf, 2014; Hu, Schwarz, and Uhan, 2012; Kim and Kwon, 2015; Volpp, 2016). These studies are the catalyst for our exploration of the issue of healthcare supply chain transparency.…”
Section: Literature Review and Research Propositionmentioning
confidence: 99%